Weak form market efficiency test of Bangladesh Stock Exchange: an empirical evidence from Dhaka Stock Exchange and Chittagong Stock Exchange - Shafir Zaman (Journal of Economics, Business, and Accountancy Ventura, 2018)
Investors need to have an idea about stock market before making investment whether the stock markets are efficient or not to take investment decision in stock market. For that reason, measurement of market efficiency of stock market bears significance to investors. Bearing it in mind, the study is undertaken to find out the existence of weak form efficiency prevails in largest stock market of Bangladesh. In order to get perfect result Parametric and Non Parametric tests were conducted of DSE & CSE for 2013 to 2017. It was found from all tests that Dhaka and Chittagong Stock exchange are not weak form efficient. Therefore, the result of the study will act as a helping hand to researchers to find out the reason of Bangladesh stock market not being weak form efficient as well as providing measurement to make the stock market weak form efficient.